Simulating stock returns under switching regimes: A new test of market efficiency - David Meenagh; Patrick Minford; David Peel (Cardiff University, Cardiff Business School, 2006)
A model of profits switches between four regimes with fixed probabilities; the rationally expected profits stream implies the stock market value. This efficient market model is not rejected by UK post-war time-series behaviour of either profits or the FTSE index.
Keywords: C15; C5; G14; 330; regime switching; stock returns; efficient markets; rational expectations; Aktienmarkt; Kapitalertrag; Politischer Wandel; Wirtschaftsmodell; Markovscher Prozess; Großbritannien; Markteffizienz